Microchannel methane steam reformers with improved heat transfer efficiency and their long-term stability. (15th July 2016) - Jin, Min-Ho; Lee, Chun-Boo; Lee, Dong-Wook; Lee, Sung-Wook; Park, Jin-Woo; Oh, Duckkyu; Hwang, Kyung-Ran; Lee, Kwan-Young; Park, Jong-Soo
Highlights: The improved heat transfer efficiency was directly reflected in the methane reforming performances. Methane conversion has increased by 71.9–86.6 %; at the same supply rate of fuel. The long-term stability of microchannel reformers was verified by methane reforming tests for 500 h. Abstract: To improve the performance of methane steam reforming as an endothermic reaction, the heat transfer efficiency from a heat source to a catalyst is a much more important factor than the reaction activity of catalyst itself on an industrial scale. In this context, microchannel reactors with combustion reaction (comb) blocks and reforming reaction (reform) blocks assembled by turns attract great attention due to their enhanced heat transfer rate. However, the even heat transfer to a catalyst bed is still a challenging topic. In this study, we improved the heat transfer efficiency of microchannel methane steam reformers by using porous-membrane-type catalysts and shifting a combustion point onto the top of the catalysts. As a result, methane conversion (conv) has increased by 14.7% at the same supply rate of fuel. Surprisingly, 1 Nm 3 h −1 of hydrogen has been produced using just 0.58 L ( H : 2.9 cm, W : 20 cm, L : 10 cm) of reactors. In addition, the long-term stability of our microchannel reformers was verified by methane reforming tests for 500 h. Therefore, our microchannel reactors are expected to be more suitable for distributed power generation based on fuel cells.